Investigation of Malaysian youth’s intention to participate in the gig economy - Hon, Jin Kang; Loh, Yi Xuan; Wong, Yun Tinn (2023)
In this study, the central theme is to investigate the intention of Malaysian Youth to participate in the Gig economy. Attitudes (ATT), Perceived Behaviour Control (PBC), Subjective Norm (SN), Pull Motivation (PLM), and Push Motivation (PSM) will be the exogenous variables (IV) in our study. Furthermore, the Theory of Planned Behaviour (TPB) and Push and Pull Theory (PPT) are uncovered to benefit this research. The targeted population in this study will be Malaysians aged 18-40. According to the shaped model, the data set from the questionnaire is subsequent to the exogenous variables (IV), such as ATT, PBC, SN, PLM, and PSM. Statistical Package for the Social Sciences, SPSS statistics will be utilized for the data analysis for this study along with descriptive and inferential analysis such as demographic, reliability, multiple regression, and so on; analysis will further be discussed in this study to discover the relationship between our endogenous variable (DV) and exogenous variables (IV). After that, the outcome from the SPSS analysis verified that all the exogenous variables (IV), such as ATT, PBC, SN, PLM, and PSM, significantly impact the endogenous variable (DV) in multiple linear regression analysis. The results showed that only Attitudes (ATT), Perceived Behaviour Control (PBC), and Push Motivation (PSM) have a significant relationship with the intention to participate in the Gig economy.